PENGARUH DIVERSIFIKASI DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN PADA TOKO RABBANI CABANG PEKANBARU - Ulya, Ade Nurul; Karneli, Okta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to determine how much influence diversification and product quality to costumer satisfactiont. Sampels in this study were taken as many as 100 respondens and techniques used pusposive sampling approach. The data in this study using survey method through questionnares filled by costumers. Data were obtained by using simple regression analysis dan multiple regression analysis. The result of this study show that product diversification has a significant impact on costumer satisfaction. Product quality has a significant impact on costumer satisfaction. And then simultaneously diversification and product quality have a significant impact on costumer satisfaction. Subsequent research is suggested to use other methods in researcing costumer satisfaction, for example through in-depth interviews of respondents.Keywords: Diversification, Product Quality, And Costumer Satisfaction